The impact of migration on earnings inequality - Osborne Jackson (Federal Reserve Bank of Boston, 2019)
This paper examines the impact of migration on earnings inequality using 1940-2015 data from the U.S. census and American Community Survey. Despite measurement challenges, I successfully replicate existing findings regarding national trends in earnings inequality and migration, and subsequently analyze regional and state patterns. Using 1940 birthplace information to instrument for migration, I find that recent immigration mildly increases the top decile earnings share, while recent in-migration and out-migration have no significant effects on such inequality. I estimate that immigration contributed 5.8 percent to the observed rise in U.S. earnings inequality from 1950 to 2015, primarily through a non-migrant channel.
Keywords: R23; F22; D31; 330; migration; earnings inequality